2021
DOI: 10.1016/j.adro.2021.100681
|View full text |Cite
|
Sign up to set email alerts
|

The Hippocampus: A New Organ at Risk for Postoperative Radiation Therapy for Bucco-alveolar Cancer? A Dosimetric and Biological Analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The basic technical movements of tennis include serving, forehand and backhand, and volley; in the modern tennis sport where the bottom line is the mainstream, forehand is the most important technical action after serving in various tennis techniques; studies have shown that, in the game, forehand hits are about 25% more often than backhand hits. Forehand is divided into closed forehand and open forehand; closed forehand requires players to have their feet perpendicular to the bottom line when hitting the ball; in the process of hitting the ball, the center of gravity of the body can be transferred from the back to the front, so that the power and speed of the shot can be greater; in a long period of time, the closed style of hitting the ball was once considered the best way to hit the ball [ 2 ]. However, with the improvement of tennis forehand technical movements and the change of racket materials, more and more tennis players are using open strokes as the main way to hit the ball, because the feet are almost parallel to the bottom line when hitting the ball with the open footwork; the upper step is omitted compared with the closed footwork, allowing players to save batting time and be able to return quickly after hitting the ball.…”
Section: Introductionmentioning
confidence: 99%
“…The basic technical movements of tennis include serving, forehand and backhand, and volley; in the modern tennis sport where the bottom line is the mainstream, forehand is the most important technical action after serving in various tennis techniques; studies have shown that, in the game, forehand hits are about 25% more often than backhand hits. Forehand is divided into closed forehand and open forehand; closed forehand requires players to have their feet perpendicular to the bottom line when hitting the ball; in the process of hitting the ball, the center of gravity of the body can be transferred from the back to the front, so that the power and speed of the shot can be greater; in a long period of time, the closed style of hitting the ball was once considered the best way to hit the ball [ 2 ]. However, with the improvement of tennis forehand technical movements and the change of racket materials, more and more tennis players are using open strokes as the main way to hit the ball, because the feet are almost parallel to the bottom line when hitting the ball with the open footwork; the upper step is omitted compared with the closed footwork, allowing players to save batting time and be able to return quickly after hitting the ball.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, mounting preclinical evidence underscored the toxicity of hippocampal irradiation [12] , [23] , [24] , [25] , [26] , [27] , [28] , while growing clinical data emphasizes the significance of HS in preserving long-term cognitive function post-radiotherapy for NPC, brain tumors, and other head and neck tumors [7] , [8] , [9] , [10] , [11] , [13] , [14] , [29] , [30] . An important longitudinal study investigated early RT-related neurotoxicity using MRI in NPC patients within six months post-RT.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral microbleeds, hippocampal atrophy, and TLN have been proposed as possible mechanisms leading to cognitive impairment after RT [ 34 36 ]; however, our retrospective study was unable to obtain comprehensive neuropsychiatric assessments in these patients. Future prospective studies may help to illustrate whether the method of RT affects cognitive or hippocampus preservation [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%